Answer:
-11n
Step-by-step explanation:
You have to combine like terms
BRAINLIEST PLEASEE
(k-9)²
=(k-9)(k-9)
=k(k)-9(k)-9(k)-9(-9)
=k²-9k-9k+81
=k²-18k+81. As a result, the product of (k – 9)2 using the perfect square trinomial rule shown on the left is k²-18k+81. Hope it help!
Answer:
14.3
Step-by-step explanation:
What you would do is add all 6 numbers together. After finding the sum, divide by 6. The 6 represents the amount of numbers in the data set. So you would find 86/6 and get 14.3333. That would be rounded to 14.3. Hope this helped!